Bioinspired and Biomimetic Nanotherapies for the Treatment of Infectious Diseases - Yang, Guoyu; Chen, Sheng; Zhang, Jianxiang (Frontiers in Pharmacology, 2019)
There are still great challenges for the effective treatment of infectious diseases, although considerable achievement has been made by using antiviral and antimicrobial agents varying from small-molecular drugs, synthetic peptides/proteins, to nucleic acids. The nanomedicine approach is emerging as a new strategy capable of overcoming disadvantages of molecular therapeutics and amplifying their anti-infective activities, by localized delivery to infection sites, reducing off-target effects, and/or attenuating resistance development. Nanotechnology, in combination with bioinspired and biomimetic approaches, affords additional functions to nanoparticles derived from synthetic materials. Herein we aimed to provide a state-of-the-art review on recent progress in biomimetic and bioengineered nanotherapies for the treatment of infectious disease. Different biomimetic nanoparticles, derived from viruses, bacteria, and mammalian cells will be first described, with respect to their construction and biophysicochemical properties. Then the applications of diverse biomimetic nanoparticles in anti-infective therapy are introduced, either by their intrinsic activity or by loading and site-specific delivery various molecular drugs. Bioinspired and biomimetic nanovaccines for prevention and/or therapy of infectious diseases are also highlighted. At the end, major translation issues and future directions of this field will be discussed.